Hispanic contact linguistics theoretical, methodological and empirical perspectives - Ortiz López, Luis A.; Guzzardo Tamargo, Rosa E.; González-Rivera, Melvin (Issues in Hispanic and Lusophone linguistics, 2020)
"This volume comprises cutting edge research on language contact and change. The chapters present a wide scope of settings in which Spanish is in contact with other languages, such as Catalan, English, and Quechua; a large breadth of geographical areas (e.g., United States, Puerto Rico, Colombia, Brazil, Argentina); and varied participant groups, ranging from dialect contacts, second-language learners and heritage speakers to balanced bilinguals and code-switchers. Taken together, the chapters provide rich empirical descriptions of data pertaining to different levels of language, diverse - naturalistic and experimental - methodological approaches to data collection, as well as theoretical implications of the findings. The interdisciplinary perspective adopted by the authors contributes to the linguistic analysis and offers important insights into theoretical linguistics in general, and into theories of sociolinguistics, language variation, bilingualism, and second language acquisition"--